An Investigation of the Evolution of Heliosheath Energetics Using a Pressure Enhancement Event Observed by IBEX - Nehpreet K. Walia; Daniel B. Reisenfeld; Lauren J. Beesley; Paul H. Janzen; Thomas K. Kim; Asher S. Merrill; Sung Jun Noh; Dave Osthus; Eric J. Zirnstein (The Astrophysical Journal)
During solar cycle 24, an increase in the solar wind (SW) dynamic pressure in late 2014 caused a sharp increase in the heliospheric energetic neutral atom (ENA) flux that was seen by the Interstellar Boundary Explorer (IBEX) at 1 au in late 2016. We study the variation of the ENA energy spectra and temperature in the heliosheath (HS) and compare it with the changes in line-of-sight-integrated ENA pressure, SW number density, speed, and SW dynamic pressure to understand the detailed physics of the energetic evolution of the HS. We use an improved map-making method and a newly developed ribbon-separation technique to obtain these physical parameters from IBEX-Hi ENA data. We find that the pressure enhancement in SW dynamic pressure leads to an increase in HS pressure, which peaks in 2018 before decreasing. The temperature in the HS steadily rises due to the SW pressure enhancement and it does not show any signs of returning to the pre-enhancement value. This indicates that hot HS plasma persists even after the pressure in the HS has started to go down. After the pressure enhancement starts dissipating, a split in the 4.3 keV ENA maps is observed due to a decrease in flux close to equator. We find that this is probably caused by a decrease in SW speed near the equator, which seems to be due to the latitudinal ordering of the SW from the opening of polar coronal holes.